Eksistensi Shinto dalam Shogatsu - Ratna Handayani; Felicia Felicia; Sonya Munadir Syah (Bina Nusantara University, 2009)
Shinto as one of traditional beliefs of Japanese people unconsciously gives much influence in the cultural activities of Japanese people. Therefore, the authors had examined the existence of Shinto in Shogatsu by distributing questionnaires to the 20 respondents of Osaka University students. The article clarifies the intensity level and purpose of Japanese people in carrying out Shogatsu, in relation to the Shinto as a traditional belief of Japanese people. By use of the library research, analytical descriptive, and questionnaire method, it can be concluded that the majority of Japanese people do the activity of Shogatsu as a custom or tradition, without understanding the real purpose of Shogatsu. Actually, Shogatsu is highly associated to Shinto elements in it.